Avaliação hemodinâmica e autonômica em filhos de pais hipertensos - Motta, Josiane Motta e (2013)
The scientific literature confirms that metabolic, autonomic and anthropometric changes are commonly present in patients with arterial hypertension (AH). Offspring of hypertensive parents show since childhood some metabolic and autonomic changes, like glucose intolerance, increased lipid and catecholamines levels and a higher blood pressure than offspring of normotensive parents. Few studies have evaluated the heart rate variability in sons of hypertensive parents.Objective. The aim of this prospective randomized study was to assess anthropometric, hemodynamic and metabolic changes as well as changes in sympathetic-vagal imbalances after carbohydrate overload in offspring of hypertensive parents. Methods. In phase one, 200 volunteers were prospectively evaluated. Their hemodynamic variables were probed with HDI (Hypertension Diagnosis Incorporation, CR2000, Eagan, USA), a stress analysis was done through social readjustment scale of Holmes-Rahe and anthropometric assessment included measurement of cervical and abdominal circumferences, evaluation of lean and fat body mass and metabolic rate through bioimpedance. Part of the group as submitted to a carbohydrates overload to evaluate the autonomic imbalance. Results. Data did not meet statistical differences in lean and fat mass as well as in neck circumference and stress evaluation for offspring of hypertensive parents and the control group. However, offspring of hypertensive parents showed higher (p<0.05) casual systolic anddiastolic pressure, abdominal circumference, body mass index pulse pressure, and basal metabolic rate. For the younger cohort, we found a positive correlation between neck circumference and pulse pressure, basal metabolic rate, uric acid, and triglycerides, as well as a negative correlation between neck circumference and HDL- cholesterol. Those correlations were stronger for neck circumference than for waist circumference. In offspring of hypertensive parents we found higher blood pressure, pulse pressure, abdominal circumference, body mass index, and an increase in sympathetic-vagal imbalance after carbohydrate overload.